TENAGA KERJA INDONESIA (TKI) DAN PERLINDUNGAN HUKUMNYA - Raja Juli Agung Widodo; M Syifa Yulianis (JURNAL LEGISIA, 2022)
The number of job seekers who are interested in working abroad continues to increase from time to time. This is because people are increasingly aware of the many job opportunities in various parts of the world that can be entered by workers from other countries, including from Indonesia, as long as these workers have the qualifications and meet the requirements as specified. The method used in this thesis is a sociological juridical approach because it describes the problem from a juridical perspective (law) / through legislation with realities on the ground / social. The work agreement is in the form of a standard contract where the clauses in the work agreement have been made by the Indonesian Manpower Service Company on the authority of the service user abroad. An employment agreement for Indonesian Migrant Workers is a legal relationship individually or by an employer (service user) with a worker (TKI) to do work abroad with the intermediary of the Indonesian Migrant Worker Service Company (PJTKI) under the guidance, protection and permission of the government.